The potential climatic range of spotted lanternfly may be broader than previously predicted - Keena, Melody A.; Hamilton, George; Kreitman, Devin (Frontiers in Insect Science, 2023)
Spotted lanternfly (Lycorma delicatula White) is an invasive planthopper that was introduced to the United States from Asia and readily spreads via human aided means. Three geographically separated populations in the United States (NJ, PA, and WV) were collected and used to assess the effects of fluctuating thermal regimes that included temperatures above or below the upper (Tmax) and lower (Tmin) developmental thresholds, respectively, on nymphal survival and development, and to determine if there was within- and among-population variation in hatch timing and temperature responses of nymphs. Nymphs exposed to temperatures > Tmax and <Tmin were able to develop when those temperatures were part of an alternating regime, even though development took longer, and the average survival was lower than that of the corresponding constant temperature. When individuals from different geographically separated populations were exposed to the same temperature regimes, there was intra- and inter-population variation in time to hatch, instar duration, and estimated Tmin values. The NJ population on average hatched earlier than the PA populations. There was 1-4°C difference in estimates of the Tmin for the first through third instars for individuals from different populations. In addition, the time in instar estimates for constant 15 and 25°C from this study were 26 and 7 days faster, respectively, than estimates from previous studies. The variability in thermal responses documented in this study is large enough to have impacts on predicted phenology and potential risk of establishment especially in areas previously considered too cold to be at risk. This new information should be incorporated into phenology and risk models to improve their predictive ability.